Detection of Hepatitis C Virus Co-Infection in Hepatitis B Virus positive patient / Muhamad Azhar Muhamad Yusof - Muhamad Yusof, Muhamad Azhar (2015)
Hepatitis C virus co-infection can become troublesome to any patient infected especially when the patient had already being diagnosed with hepatitis B virus infection. It was estimated that 130 million people globally has been infected with hepatitis C virus (HCY) and mostly of the patient serve as reservoir for transmission to healthy people. While in ASEAN region, there was no significant study was done for the HCY infection among the population. The study is done to identify HCY co-infection in positive Hepatitis B virus (HBY) patient among the Malaysian population. In this study, the total number of HBY patient that is positive with HCY co-infection is 14 out of37 that account 37.84 % from the total sample. Whereas, another about 62.16 % (23 people) not developing HCY co-infection phenomena in patient with positive HBY infection. From other point of view, the distribution of hepatitis C virus detection between gender of the patient that is 9 female patient (24.3%) and 5 male patient (13.5%).Based on the race demographic data, it revealed that Chinese have the highest number of HCY positive detection that is 6 people (6.2 %), followed by Malay with 5 people (13.5%), Other races with 2 people (5.4%) and lastly Indian race with 1 person (2.7%). Based on the data between the number of HCY detection among the different diagnosis of HBY positive patient, 7 people (18.9%) with hepatitis disease positive with HCY detection by using real time PCR, followed by 5 (13.5%) people with chronic hepatitis disease, 2 (5.4%) people with cirrhosis disease and none from the people with hepatocellular carcinoma infect with HCY. The use of real time PCR assay had demonstrated a highly sensitive and specific method to detect HCY in patient sample with positive HBY virus. As for the conclusion, the result produce clearly show that the HCY can became a co-infection to the patient that had already being infect with HBY. Keywords: detection, hepatitis C virus, co-infection, hepatitis B virus, positive